2016
DOI: 10.1063/1.4952928
|View full text |Cite
|
Sign up to set email alerts
|

Energy dispersive detector for white beam synchrotron x-ray fluorescence imaging

Abstract: Abstract.A novel, "single-shot" fluorescence imaging technique has been demonstrated on the B16 beamline at the Diamond Light Source synchrotron using the HEXITEC energy dispersive imaging detector. A custom made furnace with 200μm thick metal alloy samples was positioned in a white X-ray beam with a hole made in the furnace walls to allow the transmitted beam to be imaged with a conventional X-ray imaging camera consisting of a 500 μm thick single crystal LYSO scintillator, mirror and lens coupled to an AVT M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In essence, the current study represents the first-time testing, to the best of our knowledge, of HEXITEC in an ordinary polychromatic x-ray beam line to detect XRF photons emitted by GNPs. The performance of HEXITEC for XRF applications was demonstrated previously under the monochromatic synchrotron x-ray environment [15,19]. On the other hand, little is known at this time regarding its performance under the benchtop setting where the use of polychromatic diagnostic energy range x-ray sources (e.g., tube voltages > 100 kVp) results in more pronounced scatter background, introducing additional complexity in detection/extraction of XRF signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, the current study represents the first-time testing, to the best of our knowledge, of HEXITEC in an ordinary polychromatic x-ray beam line to detect XRF photons emitted by GNPs. The performance of HEXITEC for XRF applications was demonstrated previously under the monochromatic synchrotron x-ray environment [15,19]. On the other hand, little is known at this time regarding its performance under the benchtop setting where the use of polychromatic diagnostic energy range x-ray sources (e.g., tube voltages > 100 kVp) results in more pronounced scatter background, introducing additional complexity in detection/extraction of XRF signals.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we noted a commercial pixelated detector system that appeared to allow for parallel XRF signal acquisition while meeting the technical requirements, especially in terms of the detector energy resolution, for the latest version of our benchtop cone-beam XFCT system [11]. This detector system, known as HEXITEC (High Energy X-ray Imaging Technology) [12][13][14], is based on a fully-spectroscopic pixelated cadmium telluride (CdTe) detector, and has been successfully used for XRF imaging with monochromatic synchrotron x-rays [15]. A recent study also reported the use of HEXITEC to create a multi-detector array for single-photon imaging applications [16].…”
Section: Introductionmentioning
confidence: 99%